KECERNAAN IN SACCO HIJAUAN LEGUMINOSA DAN HIJAUAN NON LEGUMINOSA DI DALAM RUMEN DAN INTESTINUM SAPI PERANAKAN ONGGOLE (PO) - , Rendi Fathoni Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to explore the optimum potential of forage, the degradation rate of nutrient of forage (legume) in the rumen and intestine which is usually provided by farmers of different forage fodder. This study used 7 different forage feedstuffs (Gliricidia leaves, Manilkara leaves, Sesbania leaves, Ficus leaves, Calothyrsus leaves, Jackfruit leaves and Cacao leaves). This research carried out 2 stages i.e. 1) observation of degradation in the rumen, and 2) observation digestibility in intestine. The data taken were the nutrient digestibility residues in rumen and intestine, including DM, OM, CP, NDF, and ADF. The samples were incubated in the rumen of fistulated cattle with different time intervals, with time/point of incubation: 2, 4, 8, 12, 16, 24, 36, and 48 hours. The samples were incubated in intestine of livestock in the canula intestine of rumen residue samples. Data were analyzes using analysis of variance unidirectional pattern, then if there were significant differences as the effect of the treatment, it were followed by Duncanâs test New Multiple Range Test (DMRT). From the calculation of in sacco rumen, it was obtained the values of DT from BK: TP 73,96%